2020
DOI: 10.1177/0706743720927830
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Intensive Inpatient Care for Severe, Resistant Obsessive-Compulsive Disorder: Résultats à long terme de soins intensifs à des patients hospitalisés pour un trouble obsessionnel-compulsif grave et résistant

Abstract: Objective: A substantial proportion of severely ill patients with obsessive-compulsive disorder (OCD) do not respond to serotonin reuptake inhibitors (SRIs) and are unable to practice cognitive behavioral therapy (CBT) on an out-patient basis. We report the short-term (at discharge) and long-term (up to 2 years) outcome of a multimodal inpatient treatment program that included therapist-assisted intensive CBT with adjunctive pharmacotherapy for severely ill OCD patients who are often resistant to SRIs and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Previous factor analysis studies in OCD have shown discrepant findings with respect to aggressive/harm & checkingrelated symptoms. While some studies have shown checking compulsions to load with aggressive obsessions (60,61), many others (32,62,63) including several from our center (12,64,65) found doubts & checking to load separately from aggressive obsessions (which loads with forbidden/taboo thoughts). In the current study "doubts" were coded separately from aggressive obsessions, which could have resulted in a factor structure different from the OCGS study.…”
Section: Discussionmentioning
confidence: 89%
“…Previous factor analysis studies in OCD have shown discrepant findings with respect to aggressive/harm & checkingrelated symptoms. While some studies have shown checking compulsions to load with aggressive obsessions (60,61), many others (32,62,63) including several from our center (12,64,65) found doubts & checking to load separately from aggressive obsessions (which loads with forbidden/taboo thoughts). In the current study "doubts" were coded separately from aggressive obsessions, which could have resulted in a factor structure different from the OCGS study.…”
Section: Discussionmentioning
confidence: 89%
“…The finding that, especially in the group of OCD patients with more severe symptoms, the Y‐BOCS‐II appeared to be more responsive is of clinical importance: It suggests that mental health care professionals can more accurately assess the effects of treatment of patients with severe OCD than was possible with the Y‐BOCS‐I. This is a noteworthy improvement because recent studies estimate that only 50% to 60% of patients with severe OCD benefit from intensive residential treatment, the currently available effective treatment option usually consisting of CBT with daily therapist guided exposure with response prevention (EX/RP), cognitive (group) therapy, additional pharmacotherapy and treatment modules (Balachander et al, 2020; Brennan et al, 2014; Siwiec et al, 2019; Veale et al, 2016). It is therefore important to be able to assess accurately and timely whether patients benefit from treatment or not.…”
Section: Discussionmentioning
confidence: 99%
“…Such programs deliver CBT with ERP and other therapies on a daily schedule with treatments lasting cumulatively for hours each day, often across 12 or more weeks. Intensive residential treatment programs appear particularly suited for treatment of severe OCD [ 110 ] and may help to achieve improvement in those who did not respond to outpatient therapy [ 111 ].…”
Section: How Should Psychotherapies Be Deployed For Ocd?mentioning
confidence: 99%